Advancing Aquaculture Integrating Microbiome Modulation, Immunomodulatory Approaches, and Mitigating Environmental Stressors in Nile Tilapia Farming - Naseer, Adeeba; Mustafa, Nadish; Iftikhar, Sara; Fareed, Zeeshan Ul Hassan; Bashir, Waqas; Khan, Kamran; Batool, Iqra; Zafar, Iram; Ali, Usman; Ather, Nimra (Indus Journal of Bioscience Research, 2024)
Sustainable aquaculture methods must be advanced to meet the problems presented by environmental stresses and the expanding worldwide need for food. This study examines cutting-edge methods for raising Nile tilapia (Oreochromis niloticus), emphasizing immunomodulatory techniques, microbiome modification, and the crucial task of reducing environmental stresses to increase resilience and production. Probiotics, prebiotics, and synbiotics are important in enhancing nutrition absorption, promoting disease resistance, and optimizing gut health, making microbiome modification an essential strategy. The use of functional feeds enhanced with bioactive chemicals and the creation of tailored vaccinations are two examples of advances in immunomodulatory approaches that have demonstrated promise in bolstering tilapia's immune systems against pathogenic threats. A holistic strategy to guarantee sustainable production is provided by simultaneously reducing environmental stresses, such as hypoxia, variable water temperatures, and pollutant exposure, through enhanced aquaculture systems, water quality control, and stress-resilient fish strains. The importance of addressing these environmental stressors is underscored, as they pose significant threats to the industry. Emerging technologies like genomics, transcriptomics, and precision aquaculture tools, which allow for the monitoring and adjusting of farming operations to suit the unique requirements of Nile tilapia, further facilitate the integration of these tactics. This review highlights the potential of comprehensive, science-driven methods in converting Nile tilapia farming into a resilient, sustainable, and fruitful enterprise and emphasizes the importance of addressing environmental stressors in this transformation.